THE ESSENCE OF EDUCATION OF CHILDREN WITH SPECIAL EDUCATIONAL NEEDS IN PRESCHOOL EDUCATIONAL ORGANIZATIONS (Web of Teachers: Inderscience Research, 2025)
This article analyzes the essence of inclusive education, its basic principles, and modern pedagogical and correctional methods in the education of children with special educational needs in preschool educational organizations. The importance of developmental and art therapy technologies in the effective organization of inclusive education is also highlighted.